Oncogenic FGFR Fusions Produce Centrosome and Cilia Defects by Ectopic Signaling - Nita, Alexandru; Abraham, Sara P; Krejci, Pavel; Bosakova, Michaela (Cells, 2021)
A single primary cilium projects from most vertebrate cells to guide cell fate decisions. A growing list of signaling molecules is found to function through cilia and control ciliogenesis, including the fibroblast growth factor receptors (FGFR). Aberrant FGFR activity produces abnormal cilia with deregulated signaling, which contributes to pathogenesis of the FGFR-mediated genetic disorders. FGFR lesions are also found in cancer, raising a possibility of cilia involvement in the neoplastic transformation and tumor progression. Here, we focus on FGFR gene fusions, and discuss the possible mechanisms by which they function as oncogenic drivers. We show that a substantial portion of the FGFR fusion partners are proteins associated with the centrosome cycle, including organization of the mitotic spindle and ciliogenesis. The functions of centrosome proteins are often lost with the gene fusion, leading to haploinsufficiency that induces cilia loss and deregulated cell division. We speculate that this complements the ectopic FGFR activity and drives the FGFR fusion cancers.
Keywords: cilie; Centrosome; Humans; Receptors, Fibroblast Growth Factor; cilia; primary cilia; cancer; lidé; zvířata; centrosome; Cilia; FGFR fusion; nádorová transformace buněk; Oncogene Fusion; fibroblast growth factor receptor; neoplastic transformation; centrosome cycle; Neoplasms; FGFR; Cell Transformation, Neoplastic; onkogenní fúze; nádory; receptory fibroblastových růstových faktorů; oncogenic driver; Animals; centrozom